Comparison of Seegene AnyPlexTM II STI-7e with standard-of-care diagnostic methods for the detection of Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis. (13th December 2022) - Bodiybadu, Kaveesha; Danielewski, Jennifer; Plummer, Erica; Bradshaw, Catriona S; Machalek, Dorothy A; Garland, Suzanne M; Vodstrcil, Lenka A; Murray, Gerald L
Abstract: The AnyPlex TM II STI-7e panel assay (Seegene) detects seven sexually transmitted organisms ( Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, M. hominis, Ureaplasma urealyticum, U. parvum, and Trichomonas vaginalis ). This study compared the performance of AnyPlex TM II STI-7e with standard-of-care diagnostic methods. Samples (cervical or vaginal swabs, or urine) from 1330 women were tested on standard-of-care assays; 83/1318 (6.3%) tested positive for M. genitalium (ResistancePlus ® MG), 99/1317 (7.5%) positive for C. trachomatis and 11/1316 (0.8%) positive for N. gonorrhoeae (Hologic ® Aptima Combo 2 ® ), and 6/689 (0.9%) positive for T. vaginalis (wet mount microscopy). AnyPlex TM II STI-7e had good agreement for the detection of M. genitalium [Cohen's kappa of 0.80, 95% confidence intervals (CI) 0.74–0.87] and C. trachomatis (kappa of 0.87, 95% CI 0.82–0.92), with positive and negative % agreement >96% for both infections. There was lower agreement for the detection of N. gonorrhoeae (kappa of 0.37, 95%CI 0.19–0.55) and T. vaginalis (kappa of 0.521, 95%CI 0.25–0.80). In summary, the test performed well in this comparison for M. genitalium and C. trachomatis detection, but results were less conclusive for N. gonorrhoeae and T. vaginalis due to low prevalence in the population.